2003
DOI: 10.1046/j.1537-2995.2003.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term hematologic reconstitution after autologous peripheral blood progenitor cell transplantation: a comparison between controlled‐rate freezing and uncontrolled‐rate freezing at 80°C

Abstract: Our study confirms that URF is safe and allows sustained long-term engraftment without increasing the risks of transplantation, even though the early engraftment after URF is slower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
6
29
0
Order By: Relevance
“…Previous reports found a similar slightly slower hematopoietic recovery when comparing stem cell cryopreservation with DMSO with or without HES, 13 with or without controlled-rate freezing 14 as well as with different concentrations of DMSO. 15 More importantly, two incidences of poor or incomplete engraftments occurred when Group DMSO 5% Group DMSO 10%…”
Section: Outcome and Long-term Follow-up Datasupporting
confidence: 59%
“…Previous reports found a similar slightly slower hematopoietic recovery when comparing stem cell cryopreservation with DMSO with or without HES, 13 with or without controlled-rate freezing 14 as well as with different concentrations of DMSO. 15 More importantly, two incidences of poor or incomplete engraftments occurred when Group DMSO 5% Group DMSO 10%…”
Section: Outcome and Long-term Follow-up Datasupporting
confidence: 59%
“…The procedures are both expensive and time-consuming. As an alternative, a simple method of cryopreservation using a mechanical freezer has been introduced for the PBSCT procedure (Makino et al 1991;Takaue et al 1994;Cilloni et al 1999;Choi et al 2001;Montanari et al 2003). One important disadvantage of uncontrolled-rate freezing is the lack of recordable data on the cooling rate.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, several groups have collaborated in the development of a simple method for the cryopreservation of PBPCs in a -85˚C mechanical freezer for autologous peripheral blood stem cell transplantation (PBSCT). Some studies on simple cryopreservation methods have shown reproducible hematopoietic recoveries after PBSCT (Makino et al 1991;Takaue et al 1994;Cilloni et al 1999;Choi et al 2001;Montanari et al 2003). Our group recently provided a freezing rate of approximately 1˚C/min for cord blood (CB) cryopreservation by storing the freezing bag in a protective aluminum canister wrapped with heatinsulating materials and placing sample tubes in a double styrene foam box inside a -85˚C electric freezer .…”
mentioning
confidence: 99%
“…However, the inevitable loss of CD34 þ cells between collection and transplant, especially during cryopreservation, is difficult to predict without assessment of the sample after cryopreservation. 4,5,7,8,18 This leads to the current debate as to whether the quantification of HPC should be performed before or after cryopreservation.…”
Section: Cd34mentioning
confidence: 99%
“…Investigators 4,5,7,8,18 who have studied post-thaw CD34 þ cells and hematopoietic recovery have found that there was a significant link between the number of CD34 þ cells after cryopreservation and neutrophil and platelet engraftment. It has been proposed 6 that the number of CD34 þ cells should be determined after cryopreservation, and that at least the loss of HPC should be monitored.…”
Section: Cd34mentioning
confidence: 99%